2020
DOI: 10.2478/bsrj-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fraud Risk Assessment on Good Corporate Governance: Case of Public Listed Companies in Oman

Abstract: Background: Fraud risk assessment as a control mechanism is becoming necessary due to continuous and never-ending fraudulent activities. Frauds arise regardless of the existence of codes for corporate governance and available control activities such as those of internal and external audit units. It is high time for the corporate governance functions such as Audit and Risk Committees and Senior Management to identify the controls, which can assist in achieving good corporate governance and at the same time prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
(22 reference statements)
0
14
0
3
Order By: Relevance
“…Accordingly, it established a securities exchange market, the Muscat Security Market (MSM), as a regular marketplace for companies and investors trading securities; and a market regulator, the Capital Market Authority (CMA) (Baatwah et al, 2018). However, like most global capital markets, companies and investors in Oman has experienced capital market shocks resulting from corporate frauds and bankruptcy (Rehman & Hashim, 2020). Thus, and responding to developed markets reforms (e.g., SOX), Omani regulatory authorities took action to recover the investors' trust in the capital market and to increase market efficiency.…”
Section: Background To the Setting Of The Studymentioning
confidence: 99%
“…Accordingly, it established a securities exchange market, the Muscat Security Market (MSM), as a regular marketplace for companies and investors trading securities; and a market regulator, the Capital Market Authority (CMA) (Baatwah et al, 2018). However, like most global capital markets, companies and investors in Oman has experienced capital market shocks resulting from corporate frauds and bankruptcy (Rehman & Hashim, 2020). Thus, and responding to developed markets reforms (e.g., SOX), Omani regulatory authorities took action to recover the investors' trust in the capital market and to increase market efficiency.…”
Section: Background To the Setting Of The Studymentioning
confidence: 99%
“…This is consistent with Saidi and Kumar (2008) who report that Oman and other GCC countries are characterized by ineffective regulations and overseeing. Also, Rehman and Hashim (2020) recently indicated that corporate governance practices by Omani public firms are a form of compliance checklist, not a strategic initiative towards sustainable future growth. Another reason, we think, is the lack of an effective internal control system and code of ethics (Rehman & Hashim, 2020).…”
mentioning
confidence: 99%
“…Also, Rehman and Hashim (2020) recently indicated that corporate governance practices by Omani public firms are a form of compliance checklist, not a strategic initiative towards sustainable future growth. Another reason, we think, is the lack of an effective internal control system and code of ethics (Rehman & Hashim, 2020). This was evidenced by several cases of fraud by managers and employees in Omani public firms (e.g., Renaissance Services in 2011; Bank Muscat in 2019; Dhofar Cattle Feed in 2020), attributed to the lack of effective internal controls or to the ethical culture (Rehman & Hashim, 2020 see for more review).…”
mentioning
confidence: 99%
“…FRA is used to deal with the risk of fraud, its impact, the potential for fraud (Rehman & Hashim, 2020). FRA is associated with increased control against potential fraud schemes, corruption, and internal and external fraud.…”
Section: Fraud Risk Assessment (Fra)mentioning
confidence: 99%
“…Fraud Risk Assessment can be considered as a core activity in all types of audits (Rehman & Hashim, 2020) both in private and public sector accounting because fraud perpetrators can come from both internal and external (Tomaš & Todorović, 2016) and also due to the impact of fraud on the sustainability of the entity (Mwangi & Ndegwa, 2020), quality of life (Whitehill, 2017) and economic growth (Simbolon et al, 2019). Several factors that can influence individuals to commit fraud are: motive, ability, opportunity, and justification (Tomaš & Todorović, 2016).…”
Section: Introductionmentioning
confidence: 99%